PWE-175 Cost-effectiveness Of Linaclotide (lin) Compared To Antidepressants (atds) In The Treatment Of Irritable Bowel Syndrome With Constipation (ibs-c) In Scotland. (9th June 2014) - Fisher, M; Walker, A; Falqués, M; Rance, M; Taylor, D; Lindner, L
Abstract : Introduction: IBS-C is a chronic functional gastrointestinal disorder that has been shown to decrease quality of life (QoL) and work productivity, and increase activity impairment. LIN is indicated by the European Medicines Agency as the only treatment for IBS-C (covering all key symptoms) in adults and has received a positive recommendation from the Scottish Medicines Consortium. This study sought to determine the cost-effectiveness of LIN compared with ATDs for the treatment of adults with moderate to severe IBS-C who have previously received antispasmodics and/or laxatives. Methods: A Markov model was created to estimate costs and quality-adjusted life years (QALYs) on 4-week cycles over a 5-year time horizon from the perspective of NHS Scotland. The comparator used was ATDs, reflecting Scottish current practice. Health states were based on treatment satisfaction (satisfied, moderately satisfied, not satisfied) and death. Transitions between states were based on satisfaction data from the LIN pivotal studies and the Scottish general all-cause mortality statistics. Treatment costs were calculated from the British National Formulary using the least-expensive ATD cost (amitriptyline hydrochloride 20 mg). NHS resource use for each state was collected from Scottish clinician interviews and combined with NHS Reference costs to obtain disease-related costs. QoL was based on the EQ-5D collected from the pivotal studies. Uncertainty was explored through extensive sensitivity analyses. Results: The base case comparing LIN with ATDs over 5 years provided an incremental cost-effectiveness ratio (ICER) value (cost per QALY) of £7, 370. Scenario analyses conducted to address structural uncertainty resulted in ICERs ranging from £1, 204 to £10, 899. Probabilistic sensitivity analysis was also conducted using 10, 000 iterations to examine parameter uncertainty over the entire model. This analysis showed that there was an 83% probability that LIN was cost-effective at a willingness to pay an ICER of £20, 000 when compared with ATDs. The mean probabilistic ICER was £4, 606 (mean incremental costs £394 and mean incremental QALYs 0.085). Conclusion: LIN is a cost-effective treatment for adults with moderate to severe IBS-C who have previously received antispasmodics and/or laxatives. The ICER in Scotland was calculated as £7, 370 when compared with ATDs and was based on conservative assumptions. Results were robust to extensive sensitivity analyses. Study funded by Almirall UK. Disclosure of Interest: M. Fisher Conflict with: former employee of WG Consulting, A. Walker Consultant for: WG Consulting, Conflict with: WG Consulting (Advisory Board meeting), M. Falqués Employee of: Almirall S. A., M. Rance Employee of: Almirall UK, D. Taylor Employee of: Ironwood Pharmaceuticals, L. Lindner Employee of: Almirall S. A.